Are Nascent Entrepreneurs Jacks-of-All-Trades? A Test of Lazear's Theory of Entrepreneurship with German Data - Joachim Wagner (Institute for the Study of Labor (IZA), 2003)
In a recent paper Edward Lazear proposed the jack-of-all-trades view of entrepreneurship. Based on a coherent model of the choice between self-employment and paid employment he shows that having a background in a large number of different roles increases the probability of becoming an entrepreneur. The intuition behind this proposition is that entrepreneurs must have sufficient knowledge in a variety of areas to put together the many ingredients needed for survival and success in a business, while for paid employees it suffices and pays to be a specialist in the field demanded by the job taken. This paper contributes to the entrepreneurship literature by empirically testing Lazear's hypothesis using a large recent representative sample of the German population. The empirical estimation takes the rare events nature of becoming a nascent entrepreneur and the regional stratification of the sample into account. The results illustrate the statistical significance and economic importance of the jack-of-all-trades theory.
Keywords: R12; J23; 330; entrepreneurship; jack-of-all-trades theory; rare events logit; Germany; Unternehmer; Selbständige; Persönlichkeitspsychologie; Schätzung; Deutschland